Musculo-skeletal function in young gymnasts: association with training loads and low-back pain - Kums, T. (Dissertationes kinesiologiae universitatis tartuensis, 22, 2008)
Musculo-skeletal function in young gymnasts: association with training loads and low-back pain One of the most actual problems waiting to be solved in sports today is the individualisation of training load, inspection of the adequacy thereof on the functional condition of an athlete`s musculo-skeletal system (MSS) with the purpose to prevent the occurence of pre-traumatic conditions. In total 133 female subjects aged 10-17 years participated in this study. Whereas 70 from them were gymnasts at national and international level, and 63 age- and gender-matched untrained girls as controls. Two main types of the MSS adaptive reaction to impact-including training loads in artistic gymnasts were observed: the positive and zero type. The positive reaction type denotes a satisfactory functional state of MSS structures, the zero type points to disturbances of their impact absorption ability. In result of applying high and even medium training loads negative changes in the functional state of MSS in young artistic gymnasts would appear. Rhythmic gymnasts demonstrated a markedly greater ability to use the potentiating effect of stretch-shortening cycle to vertical jumping performance than control subjects during DJ, but not during SMJ. The rhythmic gymnasts produced greater mechanical power during repetitive jumping maximal exercise, but fatigued faster than controls. Rhythmic gymnasts had, the more rigid vertebral column, flattened in thoracal and lumbar part that associated with imbalance in trunk muscle tone and LBP. Rhythmic gymnasts with idiopathic LBP had flattened spinal curvature in thoracal and lumbar part and more reducad disc height in thoracal and lumbar part. Disc height reduction is not even related to early degeneration in gymnasts with idiopathic LBP, but it is a result of functional overloading of the spine.